In-Vitro Study of Polysulfone-polyethylene glycol/chitosan (PEG-PSf/CS) Membranes for Urea and Creatinine Permeation - Mohd Hafiz Dzarfan Othman; Agung Abadi Kiswandono; Retno Ariadi Lusiana; Nurwarrohman Andre Sasongko; Vivi Dia A. Sangkota; Nor Basid Adiwibawa Prasetya; Parsaoran Siahaan (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2020)
High concentrations of creatinine and urea in the blood can be removed by dialysis using semipermeable membranes that are selective for certain species and hold other species through diffusion processes. This ability requires a membrane that has an active side, which functions as a targeted species identifier. The membrane must be biocompatible because the membrane will be in direct contact with the body’s biological systems. The membrane material that is made must be acceptable to the blood system so that there is no rejection from the body and have a large contact area to obtain an effective diffusion process. For this reason, a hollow fiber membrane (HFM) is needed. One of the synthetic polymers used as the base material for HFM is PSf. PSf has mechanical strength, heat resistance, and is easily formed into HFM. However, PSf has disadvantages such as lack of active side and less compatible with blood due to its hydrophobic properties. Modification using PEG and chitosan will reduce the hydrophobicity of the PSf. Membrane results were analyzed the physical, chemical, and transportability for urea and creatinine. The results of functional group characterization by FTIR show that the modification reaction was successfully carried out on polysulfone to produce PEG-PSf/CS. The modification succeeded in making the PSf membrane more hydrophilic, as evidenced by a decrease in the contact angle from 69.4° (PSf) to 53° (PEG-PSf/CS). Water uptake capability increases to 609%, and membrane porosity increases porosity increased from 72 to 83%. The water flux is also increased. Creatinine clearance ability increases from 0.09 mg/dl to 0.25 mg/dL. Urea clearance ability increases from 2.3 mg/dL to 3.07 mg/dL. The SEM image showed that the modification makes the membranes more porous.